2017
DOI: 10.22192/ijcrcps.2017.04.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of mixed ligand complexes of pyruvic acid thiosemicarbazone and acetone semicarbazone with transition metals

Abstract: The mixed ligand complexes of the type [ML1L2]Cl2. Where M=Cr(III), Mn(II), Co(II),Ni(II) and Cu(II) with L1= Pyruvic acid thiosemicarbazone L2=Acetone semicarbazone, have been synthesized, by the reactions of metal chlorides with two different semicarbazones in 1:1:1 molar ratios. The resulting products have been characterized on the basis of elemental analysis, magnetic measurement, IR and Electronic spectra, conductivity measurement, thermal analysis, antimicrobial activities. The metal complexes show ratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 7 publications
(7 reference statements)
0
3
0
Order By: Relevance
“…Materials and methods The 1 H and 13 C NMR spectra were recorded on a Bruker DRX-400. Chemical shifts are measured in ppm relative to tetramethylsilane, as solvents were used CDCl 3 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Materials and methods The 1 H and 13 C NMR spectra were recorded on a Bruker DRX-400. Chemical shifts are measured in ppm relative to tetramethylsilane, as solvents were used CDCl 3 .…”
Section: Methodsmentioning
confidence: 99%
“…8,9 Pyruvic acid is a natural product found in Populus tremula , Macrobrachium nipponense , and other organisms. Pyruvic acid thiosemicarbazone and its complexes exhibit various types of biological activity: antimicrobial, 10,11 antifungal, 12,13 cytotoxic, 14 and antitumor. 15 The complexes were more active than the uncoordinated thiosemicarbazone and even exceeded the activity of medicinal compounds used as standards.…”
Section: Introductionmentioning
confidence: 99%
“…The ligand and complex were found to be potent for anticancer activities in vitro against QSG7701 and HepG2 carcinoma cells. Shirode et al [93] reported Ni(II) complex (Fig. 16) base ligand and its complex were found to be biologically active against the bacteria E. coli and P. aeruginosa.…”
Section: Biological Importance Of Semicarbazones and Thiosemicarbazonesmentioning
confidence: 99%